1999
DOI: 10.1097/00043426-199905000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Sites in Stage IV and IVS Neuroblastoma Correlate With Age, Tumor Biology, and Survival

Abstract: Metastatic pattern in neuroblastoma differs with age and correlates with tumor biological features and EFS. These correlations could reflect changes in host or tumor biological features with age resulting in differences in metastatic capacity or tumor affinity for specific sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
267
2
12

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 382 publications
(291 citation statements)
references
References 21 publications
10
267
2
12
Order By: Relevance
“…Tumor samples from the time of diagnosis were examined in 16 patients and showed a predominance of genetic changes connoting very high-risk disease. MYCN amplification was correlated significantly with CNS recurrence, as in the report of DuBois et al, 1 which differs from the report of Kramer et al, 2 who found that only 4 of 11 children had MYCN-amplified tumors, the usual percentage in a Stage 4 high-risk population. Seven patients had detailed studies of their tumor genetics by CGH and demonstrated, in addition to 2p24 amplification, multiple poor prognostic changes, such as gain of 17q and losses of 1p and 11q.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Tumor samples from the time of diagnosis were examined in 16 patients and showed a predominance of genetic changes connoting very high-risk disease. MYCN amplification was correlated significantly with CNS recurrence, as in the report of DuBois et al, 1 which differs from the report of Kramer et al, 2 who found that only 4 of 11 children had MYCN-amplified tumors, the usual percentage in a Stage 4 high-risk population. Seven patients had detailed studies of their tumor genetics by CGH and demonstrated, in addition to 2p24 amplification, multiple poor prognostic changes, such as gain of 17q and losses of 1p and 11q.…”
Section: Discussioncontrasting
confidence: 59%
“…Headache, nausea, and emesis were associated with parenchymal disease; whereas patients with meningeal disease presented more often with pain, fever, or motor signs. We found a slightly greater proportion of patients with meningeal involvement (65%) compared with what is reported in the literature (47%), [1][2][3][4][12][13][14][15] and this value might have been even greater if routine spinal MRI studies had been performed. The time to CNS recurrence in the literature ranged from 2 months to 34 months, with median similar to the 14 months reported here.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Also, possibly as a consequence of the PI3K/Akt pathway inhibition, N-myc protein levels were also reduced in response to ARC treatment. This is especially significant given the fact that one-third of neuroblastoma tumors shows amplification of N-myc, which has a strong correlation with chemotherapy resistance (Norris et al, 1996;DuBois et al, 1999). Though it is still possible that in addition to antagonizing the prosurvival pathways indicated above, ARC-induced apoptosis may also involve as yet unrecognized events, our data provide at least a partial picture of the mechanism of action of ARC and suggest that it could be an attractive candidate for drug development against neuroblastoma tumors.…”
Section: Targeting Akt In Neuroblastoma Cells Sk Radhakrishnan Et Almentioning
confidence: 99%